Tuberous Sclerosis Complex Associated with Heterotopic Ossification in a Young Girl - Teck-King Tan; Fong-Lin Chen; Ji-Nan Sheu; Shan-Ming Chen; Hsin-Hui Huang; Jeng-Dau Tsai (Pediatrics and Neonatology)
Tuberous sclerosis complex (TSC) is a multisystem disorder resulting in hamartomatous lesions. Despite diverse manifestations, skeletal muscular comorbidity is rarely reported in TSC. We report a 2-year-old girl with TSC who suffered from multiple subcutaneous masses over the paraspinal and bilateral scapular areas, which caused disabling pain on any passive movement. Three-dimensional computed tomography scanning revealed multiple calcifications that were consequently diagnosed as fibrodysplasia ossificans progressiva. Such imaging features should be evaluated cautiously to avoid unnecessary surgical intervention and biopsy that may worsen the condition.